Board Game Design to Understand the National Power Mix - Noritaka Yusa; Ryoju Hamada (MDPI AG, 2023)
This study reports a board game design that would be an effective tool for teaching and learning the best mix of national power sources in a class concerning energy and sustainability in higher education courses. A board game was developed to understand the characteristics of power sources from a Japanese viewpoint based on an earlier study of the authors. The purpose of the game is to satisfy electricity demands by choosing power sources and procuring the resources necessary for power generation to help develop a country. A total of 50 undergraduate and graduate students were asked to assess the game. The results of the questionnaire-based survey conducted after the game confirmed the students' evaluation that the game was highly enjoyable and could serve as an effective tool for energy and environmental education in high schools or universities. In addition, the average of "the ratio of the power sources proper to win the game" given by the students was similar to Japanese power mix before the Fukushima disaster, although the game significantly simplified, and even excluded, various factors affecting the national policy of power sources.